Pengaruh Kuat Arus Pengelasan Dua Layer dengan Metode GTAW dan SMAW terhadap Kekuatan Tarik pada Plat ASTM A 36 - Awali, Jatmoko; Irawan, Yudy Surya; Choiron, Moch. Agus (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2014)
Welding is a combining method of two materials by using thermal energy. It was divided into several groups including the classification of the liquid, press and soldering. Arc welding is the most commonly used in every time, such as welding with consumable and not consumable electrodes. Two types of arc welding have deficiency and excess, respectively; combining both types of arc welding is needed to cover each other’s excess. The method in this research was combining of welding GTAW (Gas Tungsten Arc Welding) and SMAW (Shield Metal Arc Welding) with variation in Root Pass and Cover Pass position. The current of GTAW with 100A, 130A, 160A, and SMAW with 65A, 80A, and 95A were used in this research. ASTM A 36 was used as the material. The plat thickness was 7mm and single V groove 600. Combining the welding GTAW-GTAW between 100A and 100A for the first and second layer has the highest tensile strength, and the lowest tensile strength was in combination of welding between GTAW-SMAW with 65A and 100A.Keywords: Tensile strength, GTAW, SMAW, two layers and ASTM A 36